1994
DOI: 10.1021/bi00171a002
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the Xenobiotic Substrate Binding Site of a Glutathione S-Transferase as Revealed by X-ray Crystallographic Analysis of Product Complexes with the Diastereomers of 9-(S-Glutathionyl)-10-hydroxy-9,10-dihydrophenanthrene

Abstract: The three-dimensional structures of isoenzyme 3-3 of glutathione (GSH) transferase complexed with (9R,10R)- and (9S,10S)-9-(S-glutathionyl)-10-hydroxy-9,10-dihydrophenanthrene [(9R,10R)-2 and (9S,10S)-2], which are the products of the addition of GSH to phenanthrene 9,10-oxide, have been determined at resolutions of 1.9 and 1.8 A, respectively. The structures indicate that the xenobiotic substrate binding site is a hydrophobic cavity defined by the side chains of Y6, W7, V9, and L12 from domain I (the GSH bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 26 publications
5
101
1
Order By: Relevance
“…We examined whether the two GST 3-3 forms, the lysine\serine form and the asparagine\cysteine form, differed in enzyme activity, because these regions, adjacent to the C-terminus, are thought to be responsible for binding of hydrophobic substrates [45]. However, we did not observe any marked variation in specific activity values with various substrates.…”
Section: Discussionmentioning
confidence: 83%
“…We examined whether the two GST 3-3 forms, the lysine\serine form and the asparagine\cysteine form, differed in enzyme activity, because these regions, adjacent to the C-terminus, are thought to be responsible for binding of hydrophobic substrates [45]. However, we did not observe any marked variation in specific activity values with various substrates.…”
Section: Discussionmentioning
confidence: 83%
“…Motif I1 is located far from the active site of GST (Figs. 4, 5); recent structural studies did not implicate any of the residues in this motif in binding of either of the substrates (Garcia-Saez et al, 1994;Ji et al, 1994). Rather, these experiments have shown that, unlike the GSHbinding site, the electrophile-binding site is formed by variable segments of the GSTs.…”
Section: Lqkmpvfvgkdg-----fplsetlaiafylas Lgkvpafesadg-----hciaesnaiamentioning
confidence: 98%
“…The catalytic diversity of mammalian cytosolic GSTs, which can exist as homo-or heterodimers, arises in part from the existence of at least eight distinct classes (named Alpha, Kappa, Mu, Omega, Pi, Sigma, Theta, and Zeta) (1,4). The glutathione-binding site (G-site) and the catalytic mechanism of these enzymes have been the targets of many investigations involving chemical modification (5)(6)(7)(8), site-directed mutagenesis (9 -14), and x-ray crystallographic analysis (15)(16)(17)(18)(19)(20)(21). On the contrary, the electrophilic substrate-binding site (H-site) of GSTs is more complex and is class-specific.…”
mentioning
confidence: 99%
“…Crystallographic studies have shown that the H-site is quite dissimilar among different classes of GSTs (15)(16)(17)(18)(19)(20)(21). For example, in GST M1-1, the H-site is a hydrophobic cavity, whereas in GST P1-1 (15), the H-site is half-hydrophobic and half-hydrophilic with functionally important water molecules (16). Only a few amino acid residues have been identified in the H-site of GSTs, and relatively little is known about the key determinants of xenobiotic substrate specificity.…”
mentioning
confidence: 99%